Low-Molecular-Weight Chitosan Supplementation Increases the Population of Prevotella in the Cecal Contents of Weanling Pigs - Yu, Ting; Wang, Yu; Chen, Shicheng; Hu, Min; Wang, Zhiling; Wu, Guozhong; Ma, Xianyong; Chen, Zhuang; Zheng, Chuntian (Frontiers in Microbiology, 2017)
Low-molecular-weight chitosan (LC) promoted growth in weaned piglets as an alternative to feed-grade antibiotics. To investigate the influence of LC supplementation on piglets’ gut microbiome and compare the differences in community composition between LC and antibiotics with ZnO addition, we assessed the cecal microbial community by 16S rRNA gene sequencing with three treatments consisting of basal diet (CTR group), basal diet with low-molecular-weight chitosan (LC group), and basal diet with antibiotic and ZnO (AZ group). LC decreased pH more than AZ did in the cecum (both compared to CTR). Beta diversity analysis showed that community structure was distinctly different among the CTR, LC and AZ treatments, indicating that either LC or AZ treatment modulated the piglet microbiota. Bacteroidetes, Firmicutes and Proteobacteria dominated the community [>98% of operational taxonomic units (OTUs)] in piglet cecal contents. Compared to CTR, both LC and AZ increased the relative abundance of Bacteroidetes while they decreased the count of Firmicutes and AZ decreased the population of Proteobacteria. In CTR the top four abundant genera were Prevotella (~10.4%), Succinivibrio (~6.2%), Lactobacillus (~5.6%) and Anaerovibrio (5.4%). Both LC and AZ increased the relative abundance of Prevotella but decreased the ratio of Lactobacillus when they compared with CTR. Moreover, LC increased the relative abundance of Succinivibrio and Anaerovibrio while AZ decreased them. The microbial function prediction showed LC enriched more pathways in the metabolism of cofactors and vitamins than CTR or AZ did. LC may potentially function as an alternative to feed-grade antibiotics in weaned piglets due to its beneficial regulation of the intestinal microbiome. Key words: Low-molecular-weight chitosan; Weaned piglets; Cecal microflora; Microbial community; 16S rDNA sequencing.